The Effect of Sanction Severity and Its Interaction With Procedural Justice - Yasrebi-De Kom, Franziska M. (Criminal justice and behavior, 2022)
Recent scholarship suggests that detention may have differential effects depending on situational factors. This longitudinal study tests an integrative theoretical framework with the aim to identify conditions under which detention deters from subsequent rule-violating behavior. We examined whether effects of experienced sanction severity on subsequent misconduct and reoffending behavior are dependent on procedural justice perceptions among Dutch adults in detention (n = 763 and n = 765, respectively). The deterrent effect of sanction severity on misconduct was dependent on procedural justice. Increased sanction severity only deterred from subsequent misconduct when treatment was perceived as procedurally neutral to just. For individuals who were detained for the first time, a similar interaction effect was observed for reoffending behavior. The results support the added value of integrating deterrence theory with situational characteristics (i.e., procedural justice) to explain sanctioning effects and suggest that correctional staffs’ relationships with individuals in detention can contribute to order in prison and beyond.